Anti-hepatitis C virus treatment may prevent the progression of liver fibrosis in non-responder human immunodeficiency virus/hepatitis C virus coinfected patients - Sagnelli,Caterina (2014)
AIM:To evaluate changes in liver histology in patients with human immunodeficiency virus/hepatitis C virus coinfection non-responders to a suboptimal Interferon+Ribavirine regimen.MATERIALS AND METHODS:We investigated 49 patients with two sequential liver biopsies: 18 were non-responders to Interferon+Ribavirine treatment (Group hepatitis C virus Rx) administered after the 1st liver biopsy who underwent a 2nd liver biopsy after a median period of 3.92 year and 31 were patients who remained untreated for hepatitis C virus disease (Group hepatitis C virus untreated) after the 1st liver biopsy because of refusal and underwent a 2nd liver biopsy after a median period of 5.05-years. Most patients in both groups were under highly active antiretroviral therapy. At the time of 1st liver biopsy similar degrees of necro-inflammation, fibrosis and steatosis were observed in both groups. Changes in liver lesions between 1st and 2nd liver biopsys were adjusted for different intervals between liver biopsys by a mathematic formula.RESULTS:Liver fibrosis did not change in 88.9% of patients in Group hepatitis C virus Rx and in 77.4% in Group hepatitis C virus untreated. A marked deterioration in liver fibrosis was observed in 5 (16%) patients in Group hepatitis C virus untreated and in none in Group hepatitis C virus treated. Necro-inflammation and steatosis remained substantially unchanged in both groups.CONCLUSION:Liver histology remained substantially unchanged in human immunodeficiency virus/hepatitis C virus patients non-responder to anti-hepatitis C virus therapy over 4 years observation, suggesting an effective anti-hepatitis C virus early treatment for all hepatitis C virus/human immunodeficiency virus coinfected patients who can reasonably tolerate therapy.